(SXRYULVXLMR OAUMFXLPDMs - (SSu}xrsga(Ssga(Sega(Smjw L}ga(Sppjws ((SA(B.(SVxga(Sorynjw(B,s, 2003)
(SXRYULVXLMFV FSL[FLUJVFLV VXUAXJDLMRV V[FELAVORV SFULBANNRP MAXAPAN]XLMFV ADRUFV VYOSFULZRUA MAXAPAN]XJ SRLRXJXA FV]XFULMR OAUMFXLPDMs
(SXRYULVXLMFV FSL[FLUJVFLV VXUAXJDLMRV V[FELAVORV SFULBANNRP MAXAPAN]XLMFV ADRUFV VYOSFULZRUA MAXAPAN]XJ SRLRXJXA FV]XFULMR OAUMFXLPDMs